ANALYSIS OF TYPES OF TEXTILE FABRICS AND THEIR QUALITY - Ergasheva Shahzoda (Scholars Digest Publishing, 2023)
The article developed an algorithm for estimating the flexural stiffness of suit threads, on the basis of which the theory of displacement of the free sections of the thread according to the flexural stiffness of purl threads with different textile and fiber compositions was experimentally determined. The difference in the flexural virginity of bale and unbalanced yarn at manufacturing enterprises was determined. The developed method and the constructed algorithm make it possible to quickly assess the bending strength of suit threads.
Keywords: stiff fabric, elongation, accumulation, deformation.